Indigenous Moral Pedagogy in Early Childhood: The Madurese Bhu' Rebbhu' Tradition and Religious Character Formation - Prastyo, Danang; Ardhana Reswari; Selfi Lailiyatul Iftitah; Abronnisail Masruroh; Siti Hajar; Mohammad Firdauz Suryana; Hutagalung, Fonny Dameaty (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
Early childhood education in culturally diverse societies has increasingly prompted attention to pedagogical models that are developmentally appropriate, culturally situated, and connected to children’s religious and moral formation. This study examines the Madurese Bhu' Rebbhu' tradition, a communal celebration of the Prophet Muhammad’s birth, as a form of indigenous moral pedagogy in early childhood education. Using an interpretive phenomenological design, data were collected at TK Islam Al-Azhar Pagendingan, Pamekasan, Madura, through semi-structured interviews with five teachers and ten parents, participatory observations of fifteen children aged 5 to 6 years, and analysis of curriculum and learning documents. The analysis followed a seven-step phenomenological procedure consisting of repeated reading, extraction of significant statements, formulation of meanings, theme clustering, exhaustive description, identification of fundamental structure, and participant validation. The findings indicate that Bhu' Rebbhu' was enacted through five structured activities: making tengka, classroom decoration, sholawat procession, prophetic storytelling, and sharing tengka. These activities were associated with children’s value internalization through cognitive understanding, affective appreciation, and behavioral practice. Rather than claiming causal improvement, the study identifies convergent patterns showing how teachers, parents, and children experienced the tradition as a multisensory, intergenerational, and symbolically mediated learning ecology. At a global level, this study contributes to discussions on culturally responsive and indigenous early childhood education by showing how a local Islamic tradition from the Global South can provide context-sensitive insights into moral and religious learning. The findings suggest that indigenous traditions may support early childhood pedagogy when they are intentionally sequenced, ethically facilitated, and sustained through continuity between school and family contexts.